The folding lady : tools and tricks for making the most of your space room by room - Liard, Sophie (Harper Design, an imprint of HarperCollinsPublishers, 2022)
"In this illustrated guide, Sophie Liard brings her expertise together and teaches you how to fold all of your household items, from boxers, leggings, and socks to sheets, towels and even napkins and wrapping paper. The Folding Lady shows you that anything is foldable and shares the inner joy that folding brings and offers extra tips on organizing drawers, desks, snack drawers, cosmetics, and more to make life a little easier and more manageable"--